EX OFFICIO HAKIM DALAM MENENTUKAN ISTERI NUSYUZ SERTA AKIBAT HUKUMNYA - Neila Hifzhi Siregar, Agus Anwar Pahutar , (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2021)
This paper begins with the decision of the Padangsidimpuan Religious Court Judges, namely divorce divorce cases by husbands who demand that they be allowed to pledge divorce of one raj'i in front of the trial. The request was answered by the wife with a claim for reconciliation demanding her rights (past livelihood, livelihood, and mut'ah). The judge of the Padangsidimpuan Religious Court ruled that Nusayz's wife and the consequences of her law were not entitled to iddah, past and mut'ah income. Then the wife filed an appeal against the Medan High Religious Court. As for the Panel of Judges of the Medan High Court of Religion, it was decided that the wife was entitled to earn a living from the iddah, the past, and the mut'ah because the wife was not shabby.Based on the research conducted by the author, it can be concluded that the reason of the Padangsidimpuan Religious Court panel of judges in their decision which stipulates nusyuz wives and wives are not entitled to receive past livelihoods, iddah livelihoods, and mut'ah as a result of the law is because the wife does not care for the husband when ill, always divorced, the wife left the house without permission from her husband until repeatedly. Whereas according to the panel of judges of the Medan High Court of Religion, in its decision stipulating that the wife is not incoherent, then the wife is given the rights in the form of past income, livelihood, and mut'ah as divorced wife. With the reason that the husband was not found to declare / request that the wife was declared to be abusive and even willing to give the wife's rights whenever she could, the wife's departure from the house due to expulsion of the husband, the first level court had granted more than the demand (exceeding her authority limit).